The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/neuonc/nov129
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive deficits in 8 to 14-year old children with cerebellar tumors using self-report measures of executive and behavioral functioning and health-related quality of life

Abstract: The PedsQL child- and parent-report and the teacher-report BRIEF and SDQ have moderately good accuracy for discriminating between children with and without a FSIQ < 80. The PedsQL could be used in a clinical setting, and the BRIEF and SDQ in an educational setting, to screen for cases with FSIQ < 80 in children treated for brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…These findings are consistent with other recent studies that have demonstrated some efficacy in using the BRIEF to detect impaired cognitive functioning in survivors of central nervous system tumors. [22, 23] The present study, however, used the BRIEF as the only surveillance measure and related these observations to some documented level of day-to-day deficiency, either in academic achievement or allocation of attentional resources. This study adds to the literature that parents are a reliable fund of information and their report may spot difficulties that affect daily functioning in the home, school, and community settings that might otherwise go undetected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with other recent studies that have demonstrated some efficacy in using the BRIEF to detect impaired cognitive functioning in survivors of central nervous system tumors. [22, 23] The present study, however, used the BRIEF as the only surveillance measure and related these observations to some documented level of day-to-day deficiency, either in academic achievement or allocation of attentional resources. This study adds to the literature that parents are a reliable fund of information and their report may spot difficulties that affect daily functioning in the home, school, and community settings that might otherwise go undetected.…”
Section: Discussionmentioning
confidence: 99%
“…[20, 21] Recent studies with pediatric brain tumor survivors have shown that the BRIEF identified working memory deficits and was an effective surveillance tool used to identify those with diminished intellectual ability. [22, 23] Brain tumor survivors generally have more severe neurocognitive effects, including both global cognitive and executive functioning, as compared to survivors of other pediatric cancers. [12] It has not been determined whether the BRIEF is a reasonable surveillance measure in pediatric leukemia patients treated without cranial radiation and who generally have meaningful, but less severe, impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported a significant association between questionnaire scores and direct assessments 48 or proposed the use of QoS questionnaires as screening tools for the presence of neuropsychological deficit 29,49 . However, this was based on observations in a mixed sample of children (malignant and benign brain tumors 48 , brain tumors and healthy controls 29,49,50 ) which may have increased the estimates of sensitivity and specificity of questionnaires compared to that which applies to a population of medulloblastoma survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a significant association between questionnaire scores and direct assessments 48 or proposed the use of QoS questionnaires as screening tools for the presence of neuropsychological deficit 29,49 . However, this was based on observations in a mixed sample of children (malignant and benign brain tumors 48 , brain tumors and healthy controls 29,49,50 ) which may have increased the estimates of sensitivity and specificity of questionnaires compared to that which applies to a population of medulloblastoma survivors. Several reports have underlined the absence of significant intercorrelations 8,9,21,51 between direct assessments and questionnaire scores and it seems that patients whose direct assessments suggest cognitive compromise do not necessarily present behavioral or cognitive difficulties on questionnaires by self-or proxy-report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation